Effect of trelagliptin on vascular endothelial functions and serum adiponectin level in patients with type 2 diabetes: a preliminary single-arm prospective pilot study. Issue 1 (December 2016) - Ida, Satoshi; Murata, Kazuya; Betou, Katunori; Kobayashi, Chiaki; Ishihara, Yuki; Imataka, Kanako; Uchida, Akihiro; Monguchi, Kou; Kaneko, Ryutaro; Fujiwara, Ryoko; Takahashi, Hiroka
Abstract Background Trelagliptin, an oral DPP-4 inhibitor, which is administered once per week and characterized by a long half-life in blood. The effects of trelagliptin on vascular endothelial functions have not been clarified to date. The objective of the present study was to examine the effects of trelagliptin on vascular endothelial functions in patients with type 2 diabetes mellitus (DM) using flow-mediated dilatation (FMD), adiponectin, and asymmetric dimethylarginine (ADMA) as evaluation indicators. Methods This study was a preliminary single-arm prospective pilot study. The subjects of this study were type 2 DM patients aged 20–74 years, who visited our outpatient department. The patients were treated with trelagliptin, and their FMD, adiponectin, and ADMA levels were measured at baseline and at 12 weeks after initial treatment to determine the changes during the study period. Results A total of 27 patients, excluding three dropouts, were included in the population for analysis. Trelagliptin treatment showed no significant changes in FMD (2.42 ± 2.7% at baseline vs. 2.66 ± 3.8% post-treatment, P = 0.785) and ADMA (0.41 ± 0.0 µg/mL at baseline vs. 0.40 ± 0.0 µg/mL post-treatment, P = 0.402). Trelagliptin treatment resulted in a significant increase of serum adiponectin level (7.72 ± 6.9 µg/mL at baseline vs. 8.82 ± 8.3 µg/mL post-treatment, P < 0.002). Conclusions In this pilot study, trelagliptin treatment showed no significant changes in FMD. On the other hand, it was believed that trelagliptin treatment may increase serum adiponectin level. Trial Registration http://www.umin.ac.jp (Trial ID UMIN000018311)